An interaction model for affect monitoring - Song, Insu; Governatori, Guido; Colomb, Robert (Springer Berlin / Heidelberg, 2004)
This paper investigates how we can precisely define what process designers are ought achieve for what they have promised and more importantly in a way that satisfies human users. Toward these goals, an interaction model for processes and an Affect Monitoring Framework (AMF) are proposed based on our analysis on speech act theory and cognitive-based emotion models. The Affect Monitoring Framework is to detect and predict negative affects on users and to resolve caused or predicted causes of negative affects automatically.